The Effects of Biochar on Exchangeable Metal Concentration in Paddy Soils - Thanh Binh, Nguyen; Nghiem, Ha Tran Quang (VNU Journal of Science: Earth and Environmental Sciences, 2023)
The presence of metals in soil may impact the environment, as well as agricultural products. Biochar can alter some physical and chemical properties of the soil, reducing the concentrations of exchangeable metals in the soil. The aim of this study was to examine the effects of biochar on the exchangeable metal concentration in two paddy soils that have different organic carbon (OC) contents. A pot experiment was conducted in a greenhouse using two soils with high (3.05%) and low (0.54%) OC content mixed with biochar at rates of 0, 1.5, 3, 6, and 12%, and planted with rice in two consecutive seasons. At the end of each season, 30 soil samples (2 soil types x 5 biochar rates x 3 replicates) were collected to determine the exchangeable concentration of Al, Fe, Mn, Cd, Ni, Pb, and Zn, as well as pH. The metal quality index was calculated using principal component/factor analysis. The results showed that biochar increased the pH value after the first rice crop but did not improve after the second rice season. Biochar reduced the exchangeable concentration of some metals, including Al, Fe, Ni, Cd, Pb, and Zn. Compared to the no-biochar treatment, biochar application increased the soil metal quality index from 4.1 to 12.8% after the first crop and from 9.6 to 188.7% after the second rice crop, depending on soil properties and used biochar rate. This effect could be related to the increased pH in biochar-added soil and biochar's adsorption capacity. In conclusion, biochar has promising prospects for reducing exchangeable metal content in arable soils, thus exhibiting the potential to be used in paddy fields to remediate metal-contaminated soils.